The Meaning of Social Reality: Positivism vs. Phenomenology in the Social Sciences - Rosen, Nicholas M. (My University, 1978)
Alongside the philosophical debate between phenomenology and positivism there is a parallel debate among social scientists. It concerns the respective merits of qualitative and quantitative research. Qualitative research has, as a model of society, a set of conceptual relationships, while quantitative research uses a purely causal empirical model.
Commencing with the intuition that society consists of both causal and conceptual relationships, an attempt is made to combine elements of both positivism and phenomenology in a way helpful to social science practitioners.
The two opposing models are held to be reconcilable at the level of social explanation, and a theoretical basis for this conclusions is presented. The two contrasting views of the nature of rationality are also discussed, and it is argued that both can be used in tandem as tools of mutual criticism and enlightenment.
Keywords: Philosophy; Philosophy